Chemical composotion and potential of Eucalyptus essential oils for control of stored product insects, Sitophilus oryzae L. and Tribolium castaneum (herbst) - Farashiani, Mohammad Ebrahim (2014)
Stored product insects, Sitophilus oryzae L. (Coleoptera: Curculionidae) and Tribolium castaneum (Herbst) (Coleoptera.: Tenebrionidae) are among of the most destructive pests of stored products and grains in different parts of the world. Fumigation of pest-infested grains and stored food product with methyl bromide and phosphine has been the most successful method in the control and management of the pests. However, extensive and uncontrolled application of these fumigants has caused serious problems such as resistance in pests and destruction effects on the ozone layer.To overcome such problems, safer options to current fumigants are being investigated. Hence, plant materials with natural pesticide properties are a subject of interest. Eucalyptus essential oils are among the safe alternative plant extracts that has the potential to be a natural pesticide. Therefore, thisstudy focuses on identifying the chemical composition of 53 Eucalyptus essential oils, studying the effects of carriers and extraction methods, screening fumigant toxicity of the oils, evaluating the influence of environmental factors on the chemical constitution and insecticidal activity of the oils, and testing selected Eucalyptus essential oils as biofumigants against S. oryzae and T. castaneum. Gas chromatography (GC) and Gas chromatography–Mass spectrometry (GC-MS) analysis of 53 Eucalyptus essential oils showed that monoterpene compounds (C10 H16) such as 1, 8- cineole, α-pinene and limonene were the major constituents (74%) of the Eucalyptus essential oils.Among the 10 chemical solvents examined for the essential oils dilution, Tween 80 was a suitable carrier for diluting the oils. The essential oils (E. camaldulensis and E. globulus) extracted by hydro-distillation showed the highest fumigant activity (LC50, 24. 89 to 27. 43 μl/l air) against S. oryzae and had the highest percentage composition of 1, 8-cineol (68.75 to 78.23%).Of the 53 Eucalyptus species essential oils screened, the oils extracted from E. camaldulensisandE. globulus had the highest fumigant toxicity (LC50 < 30 μl/l air) againstS. oryzae. The main compound of Eucalyptus essential oil, 1,8-cineole showed considerable fumigant toxicity against S. oryzae (LC50 = 26.59 μl/l air), and multiple regression analysis revealed a strong correlation (41%) between the fumigant toxicity of essential oils and their 1,8- cineole concentration. Environmental factors such as climate condition and tree age influenced the fumigant toxicity of E. camaldulensis and E. globulus essential oils against S. oryzaesignificantly. The LC50 values of the oils from the north of Iran (31.72, 27.43 μl/l air) was significantly higher than the LC50 values of the oils from the south of Iran (41.5, 38.42 μl/l air). The fumigant toxicity (LC50) of the oils extracted from 20 year old trees (24.45, 26.77 μl/l air) were also notably higher than the oils from five year old trees (30.36, 36.80 μl/l air). Toxicity studies showed that E. camaldulensis and E. globulus essential oils had strong fumigant toxicity toward adults of S. oryzae(LC50,24.90 - 27.43 μl/l air) and T. castaneum(LC50 , 37.61 - 38.09μl/l air), and that they acted very fast (LT50 , 2.15 to 3.09 hours) against the insects at 250 μl/l dose. Both oils highly repelled the insects and at 2.5 μl/ml (μl essential oils/ml acetone/40kernels), their repellency values against S. oryzae and T. castaneum were more than 90%. Persistency of the oils against the insects was notable and LT50 values of the oils at the 100 μl/l dosage were in the range of 5.94 to 7.54 days. Based on the significant insecticidal activities of the selected Eucalyptus essential oils, it was evident that E. camaldulensis and E. globulusessential oils have great potential for future development as safe fumigants.